Bioactive drimane sesquiterpenoids and isocoumarins from the marine-derived fungus Penicillium minioluteum ZZ1657. Issue 7 (13th February 2020) - Ma, Mingzhu; Ge, Hengju; Yi, Wenwen; Wu, Bin; Zhang, Zhizhen
Graphical abstract: Highlights: Four new compounds were isolated from the marine Penicillium minioluteum ZZ1657. Purpurides E and F are the first example of this type of the drimane sesquiterpenoids. Purpurides E and F showed antibacterial and antifungal activities. Purpuride G had antiproliferative activity against glioma cells. Abstract: Four new compounds, including three drimane sesquiterpenoids purpurides E–G (1 –3 ) and one isocoumarin peniisocoumarin H (4 ), together with 15 known compounds, were isolated from the marine-sourced fungus Penicillium minioluteum ZZ1657. Their structures were elucidated by a combination of the HRESIMS data, extensive NMR spectroscopic analyses, and single crystal X-ray diffractions. Purpurides E (1 ) and F (2 ) are two N -acetyl-l -valine-conjugated drimane sesquiterpenoids and showed antimicrobial activities against methicillin-resistant Staphylococcus aureus, Escherichia coli, and Candida albicans with MIC values of 6–12 and 3–6 μg/mL, respectively. Purpuride G (3 ) showed antiproliferative activities against human glioma U251 and U87MG cells with IC50 values of 4.49 and 10.9 μM, respectively.